Cost-effectiveness Analysis of Clinical Specialist Outreach as Compared to Referral System in Ethiopia: An Economic Evaluation - Kifle, Yibeltal A; Nigatu, Tilahun H (BioMed Central, 2010)
Background In countries with scarce specialized Human resource for health, patients are usually referred. The other alternative has been mobilizing specialists, clinical specialist outreach. This study examines whether clinical specialist outreach is a cost effective way of using scarce health expertise to provide specialist care as compared to provision of such services through referral system in Ethiopia. Methods A cross-sectional study on four purposively selected regional hospitals and three central referral hospitals was conducted from Feb 4-24, 2009. The perspective of analysis was societal covering analytic horizon and time frame from 1 April 2007 to 31 Dec 2008. Data were collected using interview of specialists, project focal persons, patients and review of records. To ensure the propriety standards of evaluation, Ethical clearance was obtained from Jimma University. Results It was found that 532 patients were operated at outreach hospitals in 125 specialist days. The unit cost of surgical procedures was found to be ETB 4,499.43. On the other hand, if the 125 clinical specialist days were spent to serve patients referred from zonal and regional hospitals at central referral hospitals, 438 patients could have been served. And the unit cost of surgical procedures through referral would have been ETB 6,523.27 per patient. This makes clinical specialist outreach 1.45 times more cost effective way of using scarce clinical specialists' time as compared to referral system. Conclusion Clinical specialist outreach is a cost effective and cost saving way of spending clinical specialists' time as compared to provision of similar services through referral system.
© 2010 Kifle and Nigatu; licensee BioMed Central Ltd. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.
Keywords: Human resource for health; Clinical specialist outreach; Ethiopia; Cost effective; Referral